Barzilai-Borwein gradient method for solving fuzzy nonlinear equations - Mohammed Sulaiman, Ibrahim; Mamat, Mustafa; Yusuf Waziri, Muhammad; Shamsidah Amzeh, Nor (International Journal of Engineering and Technology, 2018)
In this paper, we employ a two-step gradient method for solving fuzzy nonlinear equations. This method is Jacobian free and only requires a line search for 15k=0"> . The fuzzy coefficients are presented in parametric form. Numerical experiments on well-known benchmark problems have been presented to illustrate the efficiency of the proposed method.Â